Microseismicity and faulting geometry in central Greece - Karakostas, V.; C. Karamanos; Papadimitriou, E.; Kassaras, I.; Makropoulos, K. (1st European Conference on Earthquake Engineering and Seismology 2006 (1st ECEES): Joint Event of the 13th European Conference on Earthquake Engineering and the 30th General Assembly of the European Seismological Commission, Geneva, Switzerland, 3–8/09/20, 2006)
During November 2004 – June 2005 a digital seismological network was deployed in the eastern part of central Greek mainland, in an area seismically active in the 20th century, particularly in the decade of fifties. The strongest earthquake (M=7.0) occurred in 1954, while the last strong one in 1980 (M=6.5). In total 18 Reftek digital loggers (both 72A–07 and R–130) were installed assembled with fifteen guralp CMG40T broadband and three Le_1Hz seismometers. The average spacing between stations was of the order of 20 km to ensure earthquake depth accuracy. Local earthquakes with P– and S– arrivals at four or more stations were located using HYPOINVERSE computer program. Data analysis using the Double Difference technique did not change considerably the spatial distribution of the earthquake foci. The best–recorded earthquakes were used to define a reasonable crustal structure. Lateral variations of the crustal model taken into account, calculating time delays for each station. By this way, earthquakes inside the network or close to its boundaries were located with high accuracy in both the epicenter and focal depth. In addition, focal mechanisms of earthquakes with proper azimuthal coverage were computed. Seismicity covers most of the area and is distributed mainly in clusters along active structures. A magnitude M=3.9 earthquake, was the largest local one recorded by this network (5 December 2004, 17:58 UTC), close to the focal area of the 1980 strong earthquake. Several cross sections striking normal to the trend of the clusters of the epicenters reveal the geometry of the active structures as well as the width of the seismogenic layer. Most of the focal mechanisms exhibit normal faulting and were used along with the microseismicity foci in the cross sections for the definition of the properties of the faults that activated during the experiment.